Longitudinal associations between parental early psychological distress and children's emotional and behavioural problems during early childhood and self-reported social functioning in 11-year-old children born very preterm - Salomäki, Susanna (Taylor & Francis, 2025)
This study examined longitudinal associations between parental psychological distress (stress and depression) when the child was 2 to 4 years and a child’s emotional and behavioural problems at ages 3 to 4, and social functioning (loneliness and social competence) at age 11 in very preterm born children. The participants were Finnish families of 172 very preterm infants (gestational age < 32 weeks and/or birth weight ≤ 1500 g). In girls, higher levels of maternal depression were associated with higher levels of social and emotional loneliness. Furthermore, higher levels of maternal stress and children’s externalizing problems were associated with lower levels of experienced empathy. In boys, higher levels of paternal depression were associated with lower levels of social loneliness and impulsive behaviour. In conclusion, early parental psychological distress is associated with early socioemotional development and the later experienced social functioning in former very preterm infants. The sex of the child moderates these associations.